Effect of Si alloying on the structural, thermal expansion, and magnetic properties of FeCoNiAlSix high-entropy alloys - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Lee, Hansung; Madavali, Babu; Ahn, Byungmin (Journal of Materials Science, 2024)
In this study, a series of FeCoNiAlSix (x = 0, 0.2, 0.4, and 0.6) high-entropy alloys (HEAs) were prepared by mechanical alloying and spark plasma sintering. The effects of Si alloying on the structural, thermal expansion, and magnetic properties of HEAs were investigated. The X-ray diffraction and microscopic results reveal that the crystal structure changes from FCC + BCC to single BCC phase with increasing Si content. By increasing Si content, the coefficient of thermal expansion decreases, especially at high temperatures, indicating that Si has a greater effect on improving the dimensional stability. In addition, the developed HEAs exhibit good saturation magnetization ~ 86.23 emu/g, low coercivity ~ 18.4 Oe, and high electrical resistivity ~ 84 µΩ.cm, indicating the present HEA can be used in soft magnetic applications. Furthermore, the hardness of HEAs increased from 510 ± 10 to 730 ± 10 HV with an increasing Si content due to formation of stable BCC phase. The present study demonstrates that alloying of Si facilitates a balance between desirable physical and mechanical properties. Graphical Abstract: (Figure presented.)
Keywords: BCC phase; Coefficient-of-thermal expansion; Crystals structures; High entropy alloys; Si content; Spark-plasma-sintering; Structure change; Thermal expansion properties; Thermal magnetic properties; X- ray diffractions